Polar mesosphere summer echoes and possible signatures of pulsating aurora detected by the meteor radar - Kozlovsky, A. (A.); Shalimov, S. (S.); Lester, M. (M.); Belova, E. (E.) (American Geophysical Union, 2021)
Abstract Using data of the all-sky interferometric meteor radar (SKiYMET, 36.9 MHz) operating in the Sodankylä Geophysical Observatory (67°22′N, 26°38′E, Finland) we found a specific type of polar mesosphere summer echo (PMSE), the power of which exhibits irregular variations at a frequency of the order of a few Hz. We classified such radar echoes as pulsating PMSE. These echoes were observed in late June-July in the morning sector (4–12 MLT) during geomagnetic storms. They were received from a narrow range of altitudes near 82 km, which corresponds to the altitude of noctilucent clouds where ice particles of about 50-nm radii exist. During pulsating PMSE, the SGO ionosonde showed an electron density of the order of 3 × 10¹¹ m⁻³ around 82 km, and enhanced D-region ionization was manifested in the cosmic noise absorption. We suggest that the power of PMSE is modulated by bursts of electron precipitation corresponding to the few-Hz internal modulation of pulsating aurora. During a short precipitation burst of 50–100 keV electrons, additional electrons can attach to the ice particles due to the presence of hyperthermal electrons according to the hypothesis proposed by Rosenberg et al. (2012, https://doi.org/10.1016/j.jastp.2011.10.011). This leads to an increase of the power of PMSE. After the burst is ended, the ice particles are deionized with a characteristic time of about 0.2 s due to attractive interaction with ions.